PENGEMBANGAN MEDIA PEMBELAJARAN BERBASIS LINKTREE DENGAN MODEL INQUIRY BASED LEARNING UNTUK MENINGKATKAN KEMAMPUAN BERPIKIR KRITIS SISWA SDN MANGKUKUSUMAN 1 TEGAL - Fidianingrum Yuniasih; Taufiqulloh; Yoga Prihatin (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
Observation data carried out at SD Negeri Mangkukusuman 1, found that the use  of learning  media has not been developed innovatively and does not support various types of intelligence from students, so that it does not attract students' interest in learning and results in low students' critical thinking skills in the content of science lessons. This research aims to develop  Linktree-based science lesson content   learning media with an Inquiry Based Learning model that meets feasible and effective criteria in improving students' critical thinking skills. This research uses a research and development (R&D) model that adopts the EDED development model which includes  the exploration, development, evaluation and dissemination stages. Data collection uses interview, observation, questionnaire, test and documentation instruments. This study involved 56 students divided into 2 groups, namely the control group which amounted to 28 students of SDN Mangkukusuman 1 class VI A and the experimental group of 28 students of SDN Mangkukusuman 1 class VI B. The results of the study showed that Linktree-based learning   media was considered very feasible by validators with an average of 91.6% in the media aspect, 94.4% in the material aspect. Linktree-based learning   media is also effective in improving students' critical thinking skills with an average difference  of pretest and posttest  scores of 28, as well as the acquisition of N-gain in the experimental group trial of 0.498 and is included in the moderate criteria. The resulting conclusion is that the development  of Linktree-based learning   media with the Inquiry Based Learning  model can meet the learning needs of students and overcome the problem of low critical thinking skills of students. Linktree-based learning   media with the Inquiry Based Learning  model is suitable for use in learning and is effective in improving students' critical thinking skills.